Serum and vitreous vascular endothelial growth factor levels in diabetic retinopathy - ÇEKİÇ, OSMAN; HAKLAR, GONCAGÜL (My University, 2022)
Purpose To research whether serum vascular endothelial growth factor (VEGF) levels could be used to evaluate diabetic retinopathy (DR) progression and to compare vitreous VEGF levels after injections of intravitreal bevacizumab (IVB), ranibizumab (IVR), and triamcinolone acetonide (IVTA) in proliferative diabetic retinopathy (PDR). Methods We enrolled a total of 91 eyes of 89 subjects (70 eyes of 68 diabetics and 21 eyes of 21 nondiabetic controls). The diabetic subjects were divided into three groups as PDR (n=28), non-proliferative diabetic retinopathy (n=20), and no-DR (n=20). Eyes with PDR (n=31) were injected with IVB (n=7), IVR (n=10), or IVTA (n=6) 3 days before vitrectomy, and eight eyes did not receive an injection. Serum and vitreous samples were collected before vitrectomy and analyzed using ELISA. Results We found the severity of retinopathy was not correlated with serum VEGF levels (P=.919, ρ=−0.011). Compared with the controls, vitreous VEGF was higher in the PDR (P<.001), whereas serum VEGF did not difer (P=.99). The controls had lower vitreous VEGF than the IVB, IVR, and noinjection subgroups (P=.01, P<.001, and P=.04, respectively). Vitreous VEGF was similar among the injected and no-injection subgroups (P=.17). Conclusions Serum VEGF levels may not directly refect retinopathy progression. Neither IVB, IVR nor IVTA could eliminate vitreous VEGF levels within 3 days before vitrectomy.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Health Sciences; GÖZ HASTALIKLARI; Klinik Tıp; Klinik Tıp (MED); OPHTHALMOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Optometri; Oftalmoloji; Optometry; Ophthalmology; Bevacizumab; Diabetic retinopathy; Ranibizumab; Triamcinolone acetonide; Vascular endothelial growth factor; Vitreous humor; INTRAVITREAL BEVACIZUMAB; INJECTION; FLUID; EYES; Bevacizumab; Diabetic retinopathy; Ranibizumab; Triamcinolone acetonide; Vascular endothelial growth factor; Vitreous humor